Correlation Between Insomnia And Primary Headache In Final-Year Students Of Nursing - Bambang Setia Kesuma; Feri Agustriyani; Septika Ariyanti (Journal of Applied Nursing and Health, 2022)
Background: Adolescents' irregular sleep patterns, use of technology, gadgets, and gaming are among the causes of insomnia. Primary headaches are regarded to be another symptom of insomnia. In this study, ordinary nursing students in their last semester will be examined to see if there is any correlation between headache frequency and insomnia. Methods: This study uses a cross-sectional approach with a quantitative descriptive correlation research design. Total sampling is the sampling method employed by 71 students who, according to responses, reported having sleeplessness. The Independent variable is insomnia. The dependent variable is Primary Headache. Instrumen use kuesionare. Results: According to the results of the univariate analysis, 60 people (84.5%) and 64 people (90.1%) had primary headaches, respectively. The bivariate analysis with the Gamma test revealed that 64 students (93.8%) at Aisyah University of Pringsewu had both primary headaches and insomnia with a P-Value =0,002 ≤ 0,05. Conclusion: it can be concluded that there is a significant correlation between insomnia and primary headaches. Students are expected to improve their sleep patterns to prevent primary headaches.